The Antioxidant Effect of Mitochondrially Targeted Antioxidant SkQ1 on the Isolated Rat Heart Model - E. A. Senokosova; S. S. Krutitsky; O. V. Gruzdev; L. V. Antonova; M. V. Skulachev; E. V. Grigoriev (Общая реаниматология)
Mitochondrially targeted antioxidants based on Skulachev ions (SkQ1) are extremely attractive for neutralizing reactive oxygen species directly in the mitochondrial matrix.The aim was to examine the antioxidant and cardioprotective status of the SkQ1 mitochondrially targeted antioxidant in an isolated rat heart model of ischemia and reperfusion after cold cardioplegia.Material and methods. The effects of different concentrations of SkQ1 (1200 ng/ml, 120 ng/ml, 12 ng/ml) were explored on isolated hearts of Wistar rats (n=50) during 240-min cold cardioplegia. The levels of oxidative stress, changes in myocardial damage markers (classical and highly specific) and cardiac function (coronary flow velocity, heart rate, systolic pressure) were assessed.Results. The use of SkQ1 at 12 ng/ml resulted in a significant neutralization of oxidative stress manifestations (P<0.05). The minimum concentration of NO metabolites (nitrates and nitrites) (36.2 [30.8; 39.8] µmol/ml) was maintained at pre-ischemic level throughout the 30-minute reperfusion period, while the malonic dialdehyde concentration (49.5 [41.1; 58.9] µmol/g) was lower compared with SkQ1 use at 120 ng/ml dose. Due to the «mitigation» of oxidative stress, intracellular enzymes and highly specific markers of myocardial damage rose more slowly during reperfusion, while cardiac function recovery occurred at a higher rate and showed stability upon restoration of perfusion.Conclusion. SkQ1 at 12 ng/ml concentration showed strong antioxidant and cardioprotective properties in an ex vivo study.